Assume that no denominator equals 0.

2+i/1-3i

= 2+i/1-3i
= (2+i/1-3i) * (1+3i/1+3i)
= (2+3i^2)/(1-9i^2)
= (2/1) - (1/3i)
= 2-1/3i(answer)

1 answer

no.... from your

(2+i/1-3i) * (1+3i/1+3i)
= (2+i)/(1-3i) * (1+3i)/(1+3i)

= (2 + 6i + i - 3i^2)/(1 - 9i^2) remember i^2 = -1

= (5+7i)/10
Similar Questions
  1. Assume that no denominator equals 0.(2x-3)^2 = 2x * 2x -3 * -3 = 4x-9(answer)
    1. answers icon 4 answers
  2. Assume that no denominator equals 0.(8y^3+27)/(2xy-10y+3x-15) I don't know how to solve this one.
    1. answers icon 1 answer
  3. Assume that no denominator equals 0.5x^3(7x)^2 = 5*7*7+x^3+x^2 = 245x^5(answer)
    1. answers icon 1 answer
    1. answers icon 0 answers
more similar questions